Clinical Picture and Microbiological Pattern in 3rd and 4th Degrees of the Pedis Classification of Diabetic Foot Infection - Sumarjo, Kusmardi; Waspadji, Sarwono; Sosrosumihardjo, Rustadi; Suhendro, Suhendro (Majalah Kesehatan Pharmamedika, 2018)
Diabetic foot infection (DFI) is one complication of diabetes mellitus that has high morbidityand mortality. The success of management of DFI is influenced by many factor. This study aimed to recognize clinical picture and microbiological pattern in 3rd and 4th degrees of the PEDIS classification. The design was a prospective cross-sectional study conducted in RSCM at March until May 2005. The clinical pictures in 52 DFI’pateints were included to the PEDIS classification with the wound’s odour and crepitation. Microbiological examination was done culture for microorganisms and the antibiotiks sensitivity test. The female were greate (55,8%) than male the greatest age group were at 51-60 years old (44,2%). Poorly controlled blood glucose was found in 88%, duration of wound 2 weeks in 56%, wound without critical-limb ischaemia in 81% with wound size 25 cm2 in 58%, with bottom of wound had reached tendons in 75%. Most of the patiens undergroune sepsis (65%), diabetic neouropathy (77%), with odour distance of ≥1 m (65%), and crepitation/gas (63%). We found 96 types of microorganism, of which the greatest number was: E.coli 17,7% with highest sensitivity towards cefepime; S.aureus 15,6% towards co-amoxyclav; Bacteroides spp 4,2% towards co-amoxyclav, sultamicillin and metronidazole.